Reforming the Ukrainian economy and state: The unfinished business - Marek D\~nabrowski (EconPol Forum, 2023)
Until 2013, Ukraine's record in reforming its economy and state was not impressive. The late start of reforms in the 1990s and their chaotic implementation led to macroeconomic and financial crises in 1993, 1998-99, 2008-09, and 2014-15, and the building of powerful oligarchic groups. The Euromaidan protest movement in 2013-14 marked a turning point in Ukrainian history, which also opened a new window of political opportunity for reforming the Ukrainian state and economy. Since 2014, reforms have accelerated, but their pace has been uneven. Several areas including the judicial system, law enforcement agencies, large share of state ownership in the economy have remained unreformed or underreformed The Russian invasion in February 2022 is causing severe material, economic, and human losses, which is increasing daily. Furthermore, martial law has meant the necessity to subordinate the entire economy and its management to military and security needs. International financial aid helps to partially close a sizeable fiscal gap resulting from the war. Ukraine will need additional international aid to rebuild its economy and infrastructure when the war ends. A strict reform conditionality should accompany this aid. Incentives for reforms will also be created by the European Union's accession process
Keywords: 330